Improvement of machinability and surface integrity during electro discharge machining of inconel 718 using nano powder suspension dielectric - Ahmad, Said (2016)
Inconel 718 is one of the most difficult to cut material due to its, high hardness, high toughness, and poor thermal conductivity results in heat concentrated in the cutting zone, making it ineffective to be processed through conventional machining. So usually, an electrical discharge machining (EDM) is chosen in order to overcome such limitations. However, EDM is known as a slow machining process. Thus, by employing powder suspension in the dielectric fluid it is believe to enhance the machining efficiency. To achieve high performance in EDM for this research, higher Peak current, Ip up to 40A, Pulse duration, ton up to 400μs and Powder concentration, Cp up to 4g/l were selected as the main parameters. Copper (Cu) and Copper tungsten (CuW) were used as an electrode. Their influence on the machinabilities of the material removal rate (MRR), electrode wear rate (EWR), and surface roughness (Ra) were experimentally investigated. Some aspect of surface integrity, such as recast layer (RL) and microhardness (MH) were also evaluated. The circulating dielectric system called High Performance EDM (HPEDM) was used when conducting the experiment incorporating powder suspension dielectric. The results have shown that, at a highest Ip=40A and the lowest ton=200μs with Cp=4g/l yields the highest MRR for both Cu and CuW electrodes. The improvement is about 32% and 50% for both electrodes when compared without powder concentration at the same parameter settings. Meanwhile, machining by using Cu electrode at Ip = 40A, ton = 400μs and Cp = 4 g/l yields the lowest EWR respectively. For the CuW electrode, lowest value of EWR was obtained at Ip=20A, ton=400μs and Cp=0g/l. The lowest Ra when EDM machining by using Cu and CuW achieved at Ip=20A, Cp=0g/l and ton=400μs and 200μs, respectively. In the case of surface integrity, both electrode shows almost similar trend. The RL thickness for both electrodes were increased with an increase of Ip, ton and Cp. The MH on the RL is much higher when compared to the base material. In the case of machinability, Cu electrode is the best option in EDM machining of Inconel 718.